Answer:
7
Explanation:
5(x - 3) = 2(x + 3) Distribute
5x - 15 = 2x + 6
+ 15 + 15 Switch sides to the liked terms
5x = 2x + 6 + 15
-2x -2x Switch sides to the liked terms
5x - 2x = 6 + 15
3x = 21 Divide
3 3
x = 7
Equation: 5(x-3) = 2(x+3)
Step 1: Simplify the equation.
5 (x − 3) = 2(x + 3)
(5)(x) + (5)(−3) = (2)(x) + (2)(3) Distribute
5x + −15 = 2x + 6
5x − 15 = 2x + 6
Step 2: Subtract 2x.
5x − 15 −2x = 2x + 6 −2x
3x − 15 = 6
Step 3: Add 15.
3x − 15 + 15 = 6 + 15
3x = 21
Step 4: Divide by 3.
Step 5: Divide 21 by 3.
The answer is x = 7.
5.1m questions
6.7m answers